The Effect of Non-Performing Financing of Mudharabah and Murabahah Financing on Profitability of Islamic Banking - Andi Bintang Maulana A; Anwar Anwar; Hety Budianty (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Sharia Bank is a business entity that collects funds from the public in the form of deposits and distributes them to the community in order to improve the standard of living of many people. This study aims to determine the effect of Non-Performing Financing (NPF) of Mudharabah financing and Murabahah financing on Sharia Banking Profitability. This research is a quantitative research type. This research data is taken from the annual report of Islamic banking and the Financial Services Authority (OJK). The research variables include the independent variable is NPF Mudharabah financing and NPF Murabahah financing and the dependent variable is Profitability. The number of samples in this study, which is 60, is an annual report from 10 Islamic Banking during 2015-2020. The analysis technique used is multiple Linear Regression. The results showed that based on the partial test of Non Performing Financing (NPF), mudharabah financing has a negative and partially significant influence on Profitability in Islamic Banking and Non Performing Financing (NPF) murabahah financing has a negative and significant influence on Profitability in Islamic Banking. and based on simultaneous tests show that Non-Performing Financing (NPF) mudharabah financing and Non Performing Financing (NPF) murabahah financing together have a negative and significant effect on profitability The dominant variable simultaneously affects the level Profitability in Islamic Banking is NPF murabahah financing.